Talking Donald Trump: A Sociolinguistic Study of Style, Metadiscourse, and Political Identity - Karlina Denistia (Linguistik Indonesia, 2019)
ISBN                : 978-1-138-24450-4 (hbk)ISBN                : 978-1-3152-7688-5 (ebk)Penulis             : Jennifer SclafaniPenerbit           : Routledge (2018)Tebal               : 105 halaman